Efficient CRISPR/Cas9-Mediated Gene Editing in an Interspecific Hybrid Poplar With a Highly Heterozygous Genome - Jie Wang; Huaitong Wu; Yingnan Chen; Tongming Yin (2020)
Although the CRISPR/Cas9 system has been widely used for crop breeding, its application for the genetic improvement of trees has been limited, partly because of the outcrossing nature and substantial genomic heterozygosity of trees. Shanxin yang (Populus davidiana × P. bolleana), is a commercially important poplar clone that is widely grown in northern China. An established transformation protocol for this interspecific hybrid enables researchers to simultaneously investigate the efficiency and specificity of the CRISPR/Cas9-mediated manipulation of a highly heterozygous genome. Using the phytoene desaturase gene (PDS) as an example, we revealed that the CRISPR/Cas9 system could efficiently edit the Shanxin yang genome. Two sgRNAs were designed and incorporated into a single binary vector containing the Cas9 expression cassette. Among 62 independent transgenic lines, 85.5% exhibited an exclusively albino phenotype, revealing the total loss of PDS function. The Illumina sequencing results confirmed the targeted mutation of PdbPDS homologs induced by CRISPR/Cas9, and small insertions/deletions were the most common mutations. Biallelic and homozygous knockout mutations were detected at both target sites of the T0 transformants. Off-target activity was detected for sgRNA2 with a frequency of 3.2%. Additionally, the SNP interference of targeting specificity was assessed based on the sequence variation among PdbPDS homologs. A single mismatch at 19- or 10-bp from the PAM was tolerated by the CRISPR/Cas9 system. Therefore, multiple homologous genes were simultaneously edited despite the presence of a mismatch between the sgRNA and the target site. The establishment of a viable CRISPR/Cas9-based strategy for editing the Shanxin yang genome will not only accelerate the breeding process, but may also be relevant for other economically or scientifically important non-model plants species.